Sarcasm in written communication: emoticons are efficient markers of intention - Thompson, Dominic; Filik, Ruth (Wiley, 2016)
Here we present two studies that investigate the use of emoticons in clarifying message intent. We look at sarcasm in particular, which can be especially hard to interpret correctly in written communication. In both studies, participants were required to make the intentions of their messages clear. In the first, they clarified the meaning of existing sentences without altering the wording; in the second, they produced their own sentences. Results provided clear evidence that tongue and wink emoticons are the principal indicators of sarcastic intent, and that ellipsis is associated more with criticism, rather than with sarcasm. These findings highlight the significant role emoticons play in clarifying message intention, compensating for the absence of non-verbal cues in written communication